Acoustic Analyses of Speech Sounds and Rhythms in Japanese- and English-Learning Infants - Yamashita, Yuko; Nakajima, Yoshitaka; Ueda, Kazuo; Seno, Takeharu; Shimada, Yohko; Hirsh, David; Smith, Benjamin A. (Frontiers in Psychology, 2013)
The purpose of this study was to explore developmental changes, in terms of spectral fluctuations and temporal periodicity with Japanese- and English-learning infants. Three age groups (15, 20, and 24 months) were selected, because infants diversify phonetic inventories with age. Natural speech of the infants was recorded. We utilized a critical-band-filter bank, which simulated the frequency resolution in adults’ auditory periphery. First, the correlations between the critical-band outputs represented by factor analysis were observed in order to see how the critical bands should be connected to each other, if a listener is to differentiate sounds in infants’ speech. In the following analysis, we analyzed the temporal fluctuations of factor scores by calculating autocorrelations. The present analysis identified three factors observed in adult speech at 24 months of age in both linguistic environments. These three factors were shifted to a higher frequency range corresponding to the smaller vocal tract size of the infants. The results suggest that the vocal tract structures of the infants had developed to become adult-like configuration by 24 months of age in both language environments. The amount of utterances with periodic nature of shorter time increased with age in both environments. This trend was clearer in the Japanese environment.